GATA2 haploinsufficient patients lack innate lymphoid cells that arise after hematopoietic cell transplantation - van Lier, Y. F.; Krabbendam, L.; Haverkate, N. J. E.; Zeerleder, S. S.; Rutten, C. E.; Blom, B.; Spits, H.; Hazenberg, M. D. (Frontiers in Immunology, 2022)
Innate lymphoid cells (ILC) are important barrier tissue immune regulators. They play a pivotal role in early non-specific protection against infiltrating pathogens, regulation of epithelial integrity, suppression of pro-inflammatory immune responses and shaping the intestinal microbiota. GATA2 haploinsufficiency causes an immune disorder that is characterized by bone marrow failure and (near) absence of monocytes, dendritic cells, B cells and natural killer (NK) cells. T cells develop normally, albeit at lower numbers. Here, we describe the absence of ILCs and their progenitors in blood and bone marrow of two patients with GATA2 haploinsufficiency and show that all subsets of ILCs appear after allogeneic hematopoietic stem cell transplantation, irrespective of the preparative conditioning regimen. Our data indicate that GATA2 is involved in the development of hematopoietic precursor cells (HPC) towards the ILC lineage.